TAI CHI: AN INTEGRATIVE PRACTICE THAT ENHANCES AUTONOMY? - Lourenço, Rita de Cássia Ferreira; Surjus, Luciana Togni de Lima e Silva (Editora Impacto Científico, 2025)
This article is based on research developed through my practice as an occupational therapist on a primary care mental health team in the municipality of Osasco, in the metropolitan region of São Paulo, state of São Paulo. Since 2012, the municipality's primary care mental health center has offered the Tai Chi Workshop activity for patients with mental health needs and for individuals who wish to participate in the practice. Due to the COVID-19 pandemic, the meetings began to take place synchronously, virtually via Google Meet, as did the Research Workshops. The overall objective of the research was to understand, from the perspective of SUS users, whether Tai Chi, as an integrative practice in the region, enhances users' autonomy in managing their care. The specific objectives were to identify what motivates users to participate in the Tai Chi workshop offered in the region; to analyze whether and how Tai Chi practice influences their health perception; To verify whether the practice of Tai Chi enhances the role of patients in care management and to develop a technical educational product for the practice of Tai Chi. The proposed method was qualitative research from the perspective of critical hermeneutics and the construction of a narrative that allows for the exposure of the nuances and meanings that permeated the entire process. We observed a convergence between the conception of health in Tai Chi and Occupational Therapy, as well as the impact of this practice on the perception of a more autonomous daily life for the participants. We found clues that point to the understanding of Tai Chi as a practice that supports subjective, relational autonomy and self-care, which provides well-being and quality of life. From the discussions in the Research Workshops, a proposal emerged to create a Zine as a Technical Product derived from the research. The aim is for the results to contribute to the strengthening of integrative and complementary practices in the SUS.DOI: https://doi.org/10.56238/edimpacto2025.060-017